Beam induced heat load instrumentation installed in LHC during the Long Shutdown 2. Issue 1 (1st May 2022) - Bradu, B; Brodzinski, K; Casas-Cubillos, J; Delikaris, D; Deschamps, J B; Le Naour, S; Pezzetti, M; Tavian, L; Tovar, A; Sisti, M; Ph Tock, J; Vauthier, N
Abstract: During the second run of the Large Hadron Collider (LHC) between 2015 and 2018, significant beam induced heat loads have been observed on the beam screens circuits impacting the cryogenic system capacity, mainly due to the electron clouds generated by the beams. To validate these measurements and to obtain precise heat load assessments and comparison with preliminary calculations based on existing hardware equipment at selected locations, it was decided to add new cryogenic instrumentation around the machine. In total, 23 Coriolis flowmeters (cold conditions), 4 thermal flowmeters (room temperature conditions) and 58 Cernox thermometers have been installed and commissioned between 2019 and 2021 during the so-called long shutdown 2 (LS2). This paper presents an overview of this project, including the commissioning of these instruments and confirming at first stage the original heat load estimations.